ASSESSMENT OF WATER QUALITY INDEX FOR GROUNDWATER IN THE KELANI RIVER BASIN, SRI LANKA - Mahagamage, M.G.Y.L.; Chinthaka, S.D.M.; Manage, P.M. (International Journal of Agriculture and Environmental Research, 2015)
Attached

Kelani river basin is one of the important river basins in Sri Lanka and it is the largest recipient of industrial wastes among all other rivers. Further, it is one of the major sources for agriculture and operation of several productions. Industrialization accumulates detrimental substances to outer environment; these pollutants can be effect on ground water directly or indirectly. Ground water demand in Sri Lanka is increasing in the production sector due to quality and inexpensive attribute of the ground water. Water Quality Index (WQI) is a key to solve the problems of data management and to evaluate management strategies for improving water quality. The paper assesses water quality characteristic Kelani river basin ground water using the Canadian Council of Ministers of the Environment Water Quality Index (CCME WQI). Thirty (30) ground water sampling locations in the Kelani river basin were selected for the WQI assessment and sampling was done for period of one year from October 2012 to September 2013. CCME WQI was applied for eighteen water quality parameters. Based on the results, the average index values and their ranks for drinking were recorded as poor (33) where water quality for Irrigation and livestock were recorded as poor (37) and excellent (100) respectively. Thus the results of the study alarming continuous water quality monitoring must be priority and need proper water quality management and strategic plan for the river basin to provide safe drinking water.
Keywords: kelani river basin; ground water; water quality management; water quality index; CCME WQI